Music and Movement in Dialogue: Exploring Gesture in Soundpainting - Minors, Helen (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2012)
Using “Soundpainting” as a case study, this paper examines how musicians and dancers can create and contribute to a dialogue between, across and within the arts. Interviews with the “Soundpainter” Walter Thompson provide a practical and applied basis for analysis, and a major goal of the article is to illustrate how music-dance dialogues are formed in this creative sign language.